2010
DOI: 10.1088/0957-0233/21/9/094015
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensing by using whispering gallery modes with hollow core fibers

Abstract: We describe temperature sensing by hollow core fibers using whispering gallery modes of a spherical microresonator. Light from a tunable laser was coupled into the input end of the hollow core fiber. Optical resonances were excited in a microsphere inserted in the modified output end. Part of the light was coupled back from the resonator into the hollow core fiber and transported back to the input end. This light was recorded via a beam splitter by a diode. The sensing principle is based on the shift of the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…This device did not rely on monitoring the microspheres WGM, instead the intensity ratio of the green emission at 522 nm and 547 nm and Boltzmann statistics were used to determine the temperature [57,104]. Another thermal point sensor was made by putting a microsphere inside the tip of a hollow-core optical fiber [105], see Fig. 12.…”
Section: Temperature Sensingmentioning
confidence: 99%
“…This device did not rely on monitoring the microspheres WGM, instead the intensity ratio of the green emission at 522 nm and 547 nm and Boltzmann statistics were used to determine the temperature [57,104]. Another thermal point sensor was made by putting a microsphere inside the tip of a hollow-core optical fiber [105], see Fig. 12.…”
Section: Temperature Sensingmentioning
confidence: 99%
“…This is a large improvement in sensitivity for thermal sensing using WGRs compared to earlier work [7]- [11]. Using FEM simulations, it was also shown that, if the microbubble is in the quasidroplet regime, the fundamental TE mode in a bubble with a 500 nm wall is estimated to experience a shift of 35 GHz/K, while the effective index is still high enough to allow efficient coupling to a tapered optical fiber.…”
Section: Discussionmentioning
confidence: 75%
“…Whispering gallery resonators are demonstrated as effective sensors for a wide range of physical effects such as changes in temperature [6]- [11], pressure [12], force [13], and refractive index [14], [15], to name just a few. With regards to temperature, typically, this is done by measuring the shift in the wavelength of the WGMs due to the thermal expansion of the resonators circumference and the change in the refractive index of the glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These applications include wall shear stress calculation [3,4]; temperature measurement [5][6][7]; biosensing [8][9][10][11][12][13]; hemozoin nanocrystals detection in aquatic environment [14]; nanoparticle detection [15]; and acceleration measurement [16][17][18]. In this paper, WGM based optical cavities are used to detect and measure the applied electric field.…”
Section: Introductionmentioning
confidence: 99%